Presence of Chlamydia abortus in colostrum, milk and vaginal discharge samples of sheep - Martínez-Serrano, María Guadalupe; Díaz-Aparicio, Efrén; Palomares-Reséndiz, Gabriela; Tórtora-Pérez, Jorge Luis; Ramírez-Álvarez, Hugo; Ortega-Hernández, Nieves; Salinas-Lorente, Jesús; Morales-Alvarez, José Francisco; Cervantes-Morali, Juan Julio César (Revista Colombiana de Ciencias Pecuarias, 2022)
Background: The main transmission route of Chlamydia abortus is by ingesting the microorganism that has been eliminated in vaginal secretions, placental membranes or abortions that contaminate the environment and, possibly, through milk and colostrum. Elimination through vaginal secretions is well documented. However, there are no reports about isolation and identification of C. abortus in the colostrum or milk of infected sheep, so it is important to determine whether or not C. abortus may be present in these secretions, which are the only food of lambs. Objective: To detect C. abortus in colostrum, milk, and vaginal secretions of sheep with a history of reproductive disorders. Methods: Colostrum, milk, and vaginal exudates were collected from 66 sheep. The samples were inoculated in mouse fibroblast cell cultures and the presence of C. abortus determined by direct immunofluorescence. Results: 19 out of 66 colostrum samples (28.7%), 14 out of 66 milk samples (21.2%) and 17 out of 66 vaginal swabs (25.7%) were positive for C. abortus. The 50 samples positive for isolation and detected by immunofluorescence, together with 42 negative samples were subjected to qPCR to amplify a fragment of the ompA gene from C. abortus. Thirty-eight of the 92 samples processed by this technique were positive for C. abortus. Conclusion: The results demonstrated the presence of C. abortus in a high proportion in colostrum, milk and vaginal secretions of infected sheep. To the best of our knowledge, this is the first field study confirming the presence of C. abortus in colostrum, which shows that excretion of Chlamydia by lactogenesis could occur in the first hours after birth.